Pengembangan Soal Numerasi Berbasis Education for Sustainable Development (ESD) untuk Mengukur Kemampuan Berpikir Kritis - Intan Wahyuna (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
One of the 21st-century skills that students need to have is critical thinking. To assess the level of success in developing students' critical thinking skills, a tool is needed to measure these abilities. This research aims to produce and develop numeracy questions based on Education for Sustainable Development (ESD) that can measure students' critical thinking abilities using Rasch model analysis aided by Ministep software. The type of this research is Research and Development (R&D) approach utilizing Thiagarajan's 4D model (1974). The research involved 75 students from grade XI at SMAN 2 Bondowoso for the academic year 2023/2024. Numeracy critical thinking questions were developed using a modified 4D model— defined, designed, and developed. The types of data collection utilized are test methods and questionnaires. The final product is a numeracy question based on ESD for high school students. The developed questions serve as tools to measure students' critical thinking abilities. These numeracy questions meet valid and reliable criteria. The testing in this research includes two rounds of limited trials and field trials. The study's findings indicate that out of the 15 developed numeracy questions, they are valid as they meet at least one validity criterion and reability with an item reliability value of 0.96, indicating the instrument's proficiency in measuring critical thinking abilities.
Reupload File Repository 19 Mei 2026_Yudi Approved by Teddy
Keywords: Question Quality; ESD-based Numeracy; Critical Thinking Abilities